Growing up in medieval London : the experience of childhood in history - Hanawalt, Barbara A., 1941- (Oxford University Press, 1993)
When Barbara Hanawalt's acclaimed history The Ties That Bound first appeared, it was hailed for its unprecedented research and vivid re-creation of medieval life. David Levine, writing in The New York Times Book Review, called Hanawalt's book "as stimulating for the questions it asks as for the answers it provides" and he concluded that "one comes away from this stimulating book with the same sense of wonder that Thomas Hardy's Angel Clare felt [:] 'The impressionable peasant leads a larger, fuller, more dramatic life than the pachydermatous king.'" Now, in Growing Up in Me